Peran Dispositional Mindfulness Dalam Mengontrol Impulsive Buying Behavior Di Era Digital Pada Generasi Z Di Kota Surabaya - Galih Danang Permadi; Kardison Lumban Batu (Diponegoro Journal of Management, 2026)
This study analyzes the influence of mindfulness, self-esteem, emotional attachment, and excitement on impulsive buying attention and its implications for impulsive buying behavior among Generation Z in Surabaya, while also testing the mediating role of impulsive buying attention. Using a quantitative causal research approach, data were collected from 133 respondents through purposive sampling, and analyzed using Structural Equation Modeling (SEM) with AMOS. The results show that emotional attachment has a positive and significant effect on impulsive buying attention, whereas self-esteem and mindfulness do not. Excitement demonstrates a negative and significant influence on impulsive buying attention. Additionally, impulsive buying attention does not significantly affect impulsive buying behavior, and none of the independent variables—emotional attachment, excitement, self- esteem, or mindfulness—exert significant direct effects on impulsive buying behavior. Consequently, no indirect (mediated) effects were observed through impulsive buying attention. These results suggest that psychological and emotional factors may shape consumers’ impulsive buying attention but are not strong enough to drive actual impulsive buying behavior. Overall, the findings contribute theoretically to the understanding of psychological influences on impulsive purchasing and offer practical implications for businesses in designing effective and relevant marketing strategies for Generation Z in the digital era.